Immersive Technology and the Elderly: A Mini-Review - Shelton, Brett E.; Uz, Cigdem (KARGER, 2015)
Technologies that provide immersive experiences continue to become more ubiquitous across all age groups.This paper presents a review of the literature to provide a snapshot of the current state of research involving the use of immersive technologies and the elderly. A narrative literature review was conducted using the ScienceDirect, EBSCOhost, Springerlink and ERIC databases to summarize primary studies from which conclusions were drawn into a holistic interpretation. The majority of the studies examined the effect of immersive technologies on elder peoples' age-related declines, including sensory and motor changes (vision, hearing, motor skills), cognitive changes and social changes. Various immersive technologies have been described and tested to address these age-related changes, and have been categorized as 'games and simulations', 'robotics' and 'social technologies'. In most cases, promising results were found for immersive technologies to challenge age-related declines, especially through the increase of morale. (C) 2014 S. Karger AG, Basel
Keywords: Immersion; Technology; Games Robotics; Social networks; RANDOMIZED CONTROLLED-TRIAL; OLDER-ADULTS; VIDEO-GAME; NURSING-HOMES; INTERVENTION; PEOPLE; LONELINESS; CHALLENGES; NETWORKS; THERAPY; Geriatrics & Gerontology